Rare SUZ12 variants commonly cause an overgrowth phenotype. Issue 4 (17th November 2019) - Cyrus, Sharri S.; Cohen, Ana S. A.; Agbahovbe, Ruky; Avela, Kristiina; Yeung, Kit S.; Chung, Brian H. Y.; Luk, Ho‐Ming; Tkachenko, Nataliya; Choufani, Sanaa; Weksberg, Rosanna; Lopez‐Rangel, Elena; ,; et al.
Abstract: The Polycomb repressive complex 2 is an epigenetic writer and recruiter with a role in transcriptional silencing. Constitutional pathogenic variants in its component proteins have been found to cause two established overgrowth syndromes: Weaver syndrome (EZH2‐related overgrowth) and Cohen‐Gibson syndrome (EED‐related overgrowth). Imagawa et al. (2017) initially reported a singleton female with a Weaver‐like phenotype with a rare coding SUZ12 variant—the same group subsequently reported two additional affected patients. Here we describe a further 10 patients (from nine families) with rare heterozygous SUZ12 variants who present with a Weaver‐like phenotype. We report four frameshift, two missense, one nonsense, and two splice site variants. The affected patients demonstrate variable pre‐ and postnatal overgrowth, dysmorphic features, musculoskeletal abnormalities and developmental delay/intellectual disability. Some patients have genitourinary and structural brain abnormalities, and there may be an association with respiratory issues. The addition of these 10 patients makes a compelling argument that rare pathogenic SUZ12 variants frequently cause overgrowth, physical abnormalities, and abnormal neurodevelopmental outcomes in the heterozygous state. Pathogenic SUZ12 variants may be de novo or inherited, and are sometimes inherited from a mildly‐affected parent. Larger samples sizes will be needed to elucidate whether one or more clinically‐recognizable syndromes emerge from different variant subtypes.